Sistema de aquisição de dados de baixo custo com arduino: termômetro de cinco pontos - Souza, João Victor Galvão do Prado (2022)
In the 21st century, the use of thermometry is essential for various sectors and activities, such as data control and analysis, but it is often an unfeasible technology due to the significant value of market thermometers, such as the Penta III thermometer, used in refrigeration, in addition to being requested in university research. Thus, the objective of this project is to develop a five-point thermometer using the Arduino platform. To assemble the prototype, an Arduino Mega 2560 board, RTC and SD shields, a display and DS18B20 temperature sensors will be used. Due to the flexibility of this system, it will be possible, in addition to showing the temperature of the sensors in real time via display, to store the data on a Micro SD card with variable frequency according to need. With the conclusion of this work, it was able to obtain a market alternative product with great technological potential, low cost and with an open source philosophy.